Governing secondary research use of health data and specimens: the inequitable distribution of regulatory burden between federally funded and industry research. Issue 1 (20th May 2021) - Spector-Bagdady, Kayte
Abstract: Some of the most promising recent advances in health research offer opportunities to improve diagnosis and therapy for millions of patients. They also require access to massive collections of health data and specimens. This need has generated an aggressive and lucrative push toward amassing troves of human data and biospecimens within academia and private industry. But the differences between the strict regulations that govern federally funded researchers in academic medical centers (AMCs) versus those that apply to the collection of health data and specimens by industry can entrench disparities. This article will discuss the value of secondary research with data and specimens and analyze why AMCs have been put at a disadvantage as compared to industry in amassing the large datasets that enable this work. It will explore the limitations of this current governance structure and propose that, moving forward, AMCs should set their own standards for commercialization of the data and specimens they generate in-house, the ability of their researchers to use industry data for their own work, and baseline informed consent standards for their own patients in order to ensure future data accessibility.